PENYULUHAN CUCI TANGAN PAKAI SABUN (CTPS) DALAM RANGKAIAN KEGIATAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA SISWA MADRASAH DINIYAH AWALIYAH (MDA) - Nasution, Nurul Hidayah; Harahap, Yanna Wari (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Washing Hands with Soap is one of the sanitation measures in Clean and Healthy Living Behavior, namely by cleaning hands and fingers using water and soap to be clean. Washing hands with soap is an effort to prevent disease. The implementation of this activity is especially in schools because it is the initial structure for creating healthy and quality human resources for the progress of the nation and state. One of the efforts to provide health education in schools is through health promotion with the Washing Hands with Soap extension method. This type of service is health promotion with counseling methods. The service was carried out at Madrasah Diniyah Awaliyah, Labuhan Labo Village, Southeast Padangsidimpuan District, Padangsidimpuan City. The population and sample of this service were 30 students. The results of this community service were enthusiastically received by MDA students which can be seen from the number of students who want to answer questions and demonstrate the steps of Washing Hands with Soap. MDA students looked orderly and in accordance with what was directed by the activity committee. This counseling activity was successfully implemented. It is recommended that health educator activities related to Washing Hands with Soap for students can be carried out more frequently and the range of information dissemination can also be expanded again so that it includes all levels of society so that students and the public know more about, understand and can practice Washing Hands with Soap activities in everyday life which can ultimately improve health status Public.